Policy-Based Dynamic Proxy Framework: An Application Level Infrastructure For Active Service Creation And Contents Delivery - Choong, Khong Neng (2003)
This thesis focuses on the dynamic proxy framework named the Chek Proxy Framework (CPF). The main objectives are to scale the existing Internet architecture by conserving the backbone bandwidth, reducing server loads, and improving the overall networking system performance, particularly the client receiving rate. These were achieved by deploying application-level proxy services within the network, to accelerate and customise the delivery of contents. The CPF is based on the 3-tier distributed computing architecture with the client and server residing at the ends of the respective networks. A dynamically appointed middle-tier system, the Dynamic Application Proxy Server (DAPS) is created ondemand and resides at the client-side network based on the designed clustering policy. The uniqueness of CPF lies on the use of voluntary client machines, instead of static and dedicated machines to host DAPS services created at runtime.